The complexity of research in Educational Leadership, contemporary methodological approaches - Díaz Delgado, Miguel Angel (2019)
This academic essay develops a debate on contemporary research in Educational Leadership, stressing the complexity of its study and locating this line as an alternative for understanding organization dynamics in the Educational field. It is proposed a categorization of theoretical orientations -operational, analytical and dialogical- that represents a contemporary approach raised on the entitative, relational and syncretic focuses; these classifications are nowadays shaping the debate in this line of research. It is concluded that complex research designs can be constructed from the theories of Educational Leadership, due the varied perspectives that give evidence of conceptual dichotomy and theoretical-methodological intertwining but, above all, its indissoluble relationship between theory and practice. This discussion can contribute to recognize the properties of the theories in question and to reanimate the debate about their limits in the construction of knowledge.